ARFMS: An AR-based WYSIWYG Filmmaking System - Chen Ling; Wenjun Zhang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
This paper proposes a novel “What You See Is What You Get” filmmaking system, called as ARFMS. It provides users with a low cost and easy to use system to make movies. Users cannot only real-time visualize the performance with computer-generated objects, but also visual effects films will be finished without post-production. After finished the screenplay, the performance will be shot on-site using an ordinary camera. CG objects will be simply and effectively controlled by natural interaction. Then users can apply the DR-marker just like an actual scene element, because it takes the advantages of marker-based and markerless-based registration approaches. This paper implements ARFMS to achieve pre-visualization and real-time finish the film using augmented reality technology. The user can perform with the CG character and stage property just like real ones. DOI : http://dx.doi.org/10.11591/telkomnika.v12i6.4582